The Role of Support Systems Towards Employee Resilience: The case Of Private Educators in Kota Kinabalu, Sabah - Steward Giman anak Stephen; Walton Wider; Helmina Thomas (Universiti Malaysia Sabah, 2022)
Employees' capacity to deal with unfavorable circumstances, such as job intensification, organizational change, and work stress, will be enhanced if they have resilience. Despite an increase in study interest in the topic of employee resilience, little is known about how essential social support at work, such as supportive leadership and co-worker support, impacts workers' capacity to survive in difficult circumstances. Therefore, this paper aims to understand the role of support systems in enhancing educators’ resilience in private sectors. It focuses on the types of support systems that the educators received that make them stay working in private college. The study was conducted among educators in three different private colleges in Kota Kinabalu, Sabah. In – depth interview was used to collect the data for this study. Thematic analysis was used to analyse the data. The findings revealed that educators stay in an organization even though faced many challenges due to the following factors: supportive leader, co-worker support and family members encouragement. The findings of this study can be applied into organization retention practices, especially during this pandemic.